Pendampingan Pembuatan Bahan Ajar Menggunakan Flipbuilder dalam Meningkatkan Kemampuan Literasi Digital Guru Sekolah Dasar - Windiyani, Tustiyana; Gani, Resyi Abdul; Sofyan S., Deddy; Padillah, Ines; Ayuni, Kharima Sekar; Liah, Rina (Universitas Pahlawan Tuanku Tambusai, 2025)
This Community Service (PkM) activity aims to improve teachers' digital literacy skills through training in making interactive teaching materials using the Flipbuilder application at SDN Dewi Sartika 2, Bogor City. Digital literacy is an important competency for teachers in responding to the development of learning technology, especially in creating teaching media that is attractive and easily accessible to students. The methodology of the activity includes the preparation stage, the implementation of training, mentoring, and evaluation using pre-test and post-test instruments to measure competency improvement. The results of the activity showed that there was a significant increase in teachers' understanding and skills in making digital teaching materials, as shown by the increase in the average score from 62 (pre-test) to 85 (post-test) and the response of teachers was mostly satisfied by 30.5%. In addition, teachers are able to produce interactive e-books based on flipbuilder that are relevant to the learning needs of the classroom. The discussion showed that hands-on approaches and intensive mentoring contribute to increasing digital literacy effectively. So the use of flipbuilders has proven to be a practical and innovative solution in supporting digital transformation in the elementary school environment, while strengthening the role of teachers as adaptive digital learning facilitators.